An efficient protocol for in vitro regeneration of peanut (Arachis hypogaea L.) cultivar L14 - Phung Thi Bich Hoa; Nguyen Hoang Tue; Phan Thi Quyen Trang; Le Thi Hang; Nguyen Quang Duc Tien; Nguyen Hoang Loc (Bioscience Journal, 2021)
The present work aims to establish an efficient protocol for in vitro regeneration of peanut (Arachis hypogaea) cultivar L14. The study showed that de-embryonated cotyledon was a suitable explant for shoot multiplication on MS medium containing 4 mg/L BAP. The highest number of shoots per explant obtained after 4 weeks of culture was up to 6.8 shoots. Shoots in vitro were able to produce a large number of approximately 11 roots on MS medium supplemented with 0.5 mg/L NAA. These results will be very useful in establishing an in vitro regeneration protocol for peanut cultivar L14 during gene transfer in the next studies to improve their disease resistance.